Physiological and Pathological Functions of Mechanosensitive Ion Channels - Gu, Yuanzheng (2014)
Rapid sensation of mechanical stimuli is often mediated by mechanosensitve ion channels. Their opening results from conformational changes induced by mechanical forces. It leads to membrane permeation of selected ions and thereby to electrical signaling. Newly identified mechanosensitive ion channels are emerging at an astonishing rate, including some that are traditionally assigned for completely different functions. In this review, we first provide a brief overview of ion channels that are known to play a role in mechanosensation. Next, we focus on three representative ones, including the transient receptor potential channel V4 (TRPV4), Kv1.1 voltage-gated potassium (Kv) channel, and Piezo channels. Their structures, biophysical properties, expression and targeting patterns, and physiological functions are highlighted. The potential role of their mechanosensation in related diseases is further discussed. In sum, mechanosensation appears to be achieved in a variety of ways by different proteins and plays a fundamental role in the function of various organs under normal and abnormal conditions.